Solution of Pantograph Differential Equations by Collocation Method using Ortho Exponential Polynomial - Norhayati, Rosli; Bilal, Muhammad; Ahmad, Ifthikar (Science and Engineering Research Support Society, 2020)
Novel matrix based on numerical technique of collocation method via truncated ortho exponential polynomial (OECM) is proposed to approximate the solution of pantograph differential equations. The applicability, reliability, and efficiency of the methodology are examined by applying the method to the pantograph differential equations. The comparison is made between the existing reported results and the present results. The proposed method shows good agreement with the existing reported method, hence indicate collocation method via truncated ortho exponential polynomial (OECM) is able to numerically simulate pantograph differential equations.